Descartes, God, eternal truths, Creation Doctrine, modality, indifference, omnipotence, essence, arithmetic, Aquinas, Adrian W. Moore. - Jonathan Head (Public Reason)
This paper offers a brief response to Patterson’s paper, ”Descartes on Modality and the Eternal Truths”, which itself is at least in part a response to Moore’s paper, ‘What Descartes ought to have thought about morality”. After reviewing some relevant points from both Patterson’s and Moore’s papers regarding the question of the divine creation of necessary truths, I focus on the possible consequences of Descartes’ understanding of divine simplicity for this interpretive debate. I argue that, by bearing Descartes’ commitment to a strong form of divine simplicity in mind, we can see how he can both be committed to a voluntaristic account of the creation of divine truths and yet indicate that God could not have created things in another way.